Patellofemoral pain and sports practice: reduced symptoms and higher quality of life in adolescent athletes as compared to non-athletes - Silva, Danilo De Oliveira [UNESP]; Coura, Maira Bergamaschi [UNESP]; Waiteman, Marina [UNESP]; Pradela, Juliana [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Magalhães, Fernando Henrique; Azevedo, Fábio Mícolis De [UNESP] (Universidade Estadual Paulista, 2016)
Patellofemoral pain (PFP) is common in athletes and physically active individuals and it is one of the most frequent knee disorders among adolescents. However, the impact of the severity of PFP symptoms on quality of life (QOL) has been barely investigated. Thus, we aimed to compare the level of PFP and the self-reported QOL between adolescent athletes and non-athletes, and to explore the relationship between the severity of PFP symptoms and QOL. Fifty-six adolescents with PFP (22 athletes and 34 non-athletes) were asked to fulfill the Anterior Knee Pain Scale (AKPS) and the QOL dimension of the Knee Outcome in Osteoarthritis Survey (KOOS). Between groups comparisons indicated that adolescent non-athletes presented higher severity of PFP symptoms and lower QOF as compared with adolescent athletes. Significant correlations between the severity of PFP and QOL were found for both groups, regardless of the athletic status.
Keywords: adolescent; quality of life; knee; physical activity; athletic performance